Penyuluhan Tumbuh Kembang Anak untuk Meningkatkan Kesadaran Kognitif Orang Tua Terhadap Perkembangan Anak Usia Dini: Studi Intervensi di Posyandu Desa Pamekaran - Akhmad Yani Surachman; Mutiara Khoerunnisa; Nasywa Aulia Kamila; M Sandi Abdurohman; Redho Riyadhon Syawwali; Nadia Nurlaila Muthmainnah; Rifqi Fauzan; Fauzi Rahman Mahfudz; Iwan Satriyo Nugroho (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Active parental involvement in monitoring child growth and development is an important foundation in efforts to improve the quality of human resources from an early age. This study aims to analyze the effectiveness of SDIDTK (Early Child Growth and Development Stimulation, Detection, and Intervention)-based counseling in improving parental understanding of early childhood development, especially cognitive aspects. The activity was conducted at Posyandu Merpati 5, Pamekaran Village, Sumedang, as part of a community service program by KKN students through a quasi-experimental approach with a pre-test and post-test design on 10 respondents, mothers of toddlers. The analysis results showed a significant increase in understanding scores, from an average pre-test of 71 to 86 in the post-test (p = 0.009). This counseling also introduced the use of the KPSP application from the Ministry of Health and a family-based structured stimulation activity model that encourages parental participation in directly supporting child development. The results of this study emphasize the importance of community-based educational strategies in improving early childhood care literacy.